DETERMINANTS OF REAL EXCHANGE RATE IN ETHIOPIA - Rao, Nandeeswara; Tolcha, TassewDufera (International Journal of Research -GRANTHAALAYAH, 2016)
Real exchange rate has direct effects on trade particularly on international trade and has indirect effects on productions and employments, so it is crucial to understand the factors which determine its variations. This study analyses the main determinants of the real exchange rate and the dynamic adjustment of the real exchange rate following shocks to those determinants using yearly Ethiopian time series data covering the period 1971 to 2010. It begins with a review of literatures on Exchange rate, real exchange rate, determinants of the real exchange rate and provides an updated background on the exchange rate system in Ethiopia. An empirical model linking the real exchange rate to its theoretical determinants is then specified. This study had employed the cointegration and vector autoregression (VAR) analysis with impulse response and variance decomposition analyses to provide robust long run effects and short run dynamic effects on the real exchange rate. Share of investment, foreign exchange reserve, capital inflow and government consumption of non-tradable goods were the variable that have been found to have a long run relationship with the real exchange rate. The estimate of the speed of adjustment coefficient found in this study indicates that about a third of the variation in the real exchange rate from its equilibrium level is corrected within a year. The regression result of VECM reveals that terms of trade, nominal exchange rate, and one period lag of capital flow were the variables significantly affects the real exchange rate in the short run. However, the impulse response and variance decomposition analysis shows a better picture of the short run dynamics. The their analysis provided evidence that the Shocks to terms of trade, nominal exchange rate, capital inflow and share of investment have persistent effects on the real exchange rate in the short run. In general the regression results of both long run and short run models mostly suggest that the fluctuations of real exchange rates are predominantly responses to monetary policies shocks rather than fiscal policy shocks.